Real and quasi heortonyms as intercultural contextualized and conceptualized names - Gałkowski, Artur (Papers in Linguistics, 2020)
The paper develops an onomastic-cognitive study of heortonyms (feast names) as special chrematonymic units which, functioning like ideonyms identifying socio-cultural initiatives, transfer contextual and conceptual content related to the object of their denomination, i.e. the semantic message encoded in them. It is proposed to classify heortonyms as names of recurrent or occasional events commemorating or drawing attention to a specific idea from the circle of non-material culture. Heortonyms are monorematic, or more often polyrematic proper names used to conceptualize feasts related to religion, and similarly qualified dedications of days in the calendar, inspired by secular or parareligious culture. Hence, the classification categorizes the studied phenomenon into two groups: “usual/real heortonymy”, falling within the scope of typical religious onymy, and “quasi-heortonymy”, whose objects function in line with the communicative principle of associative evocation based on the (para)religious formula and the pattern of social campaigns. The analysis of these two types of heortonyms has an intercultural character, assuming that both real and quasi-heortonyms belong simultaneously to various cultures and have the potential to penetrate other cultural areas, depending on the context, entering religious, ideological, social, commercial and creative-media-related discourse. The discussion and conclusions are results of a cognitive analysis of Polish and English real and quasi-heortonymic units derived from data recorded in religious and secular calendars of global culture, mostly related to Western civilization. The research has an added value presenting an onomastic- terminological opinion on the definition and the scope as well as on the correlation of heortonyms with other structures of ideative chrematonymy or chrononymy.